Parvovirus Infection-Related Anemia after Kidney Transplantation - Neeraj Sharma; Ranvir Bajwa (Case Reports in Transplantation)
Anemia postkidney transplantation is an important issue which has been correlated with increased hospitalizations and higher mortality. Infections, including those due to parvovirus B19, CMV, and BK virus (polyomavirus), have also been associated with an increased risk of anemia. Here, we present a case of new-onset anemia in a kidney transplant recipient within 3 months of transplant. The patient was found to have multiple viral infections from parvo B19, BK virus, and rhinovirus. The anemia resolved completely after successful reduction in the parvo B19 and BK viral load. Workup for viral infections must be considered in the differential diagnosis of postkidney transplant anemia.